Abandonment of pearl millet cropping and homogenization of its diversity over a 40 year period in Senegal - Olodo, Katina F.; Barnaud, Adeline; Kane, Ndjido A.; Mariac, Cédric; Faye, Adama; Couderc, Marie; Zekraouï, Leïla; Dequincey, Anaïs; Diouf, Diégane; Vigouroux, Yves; Berthouly-Salazar, Cécile (PLOS ONE, 2020)
Cultivated diversity is considered an insurance against major climatic variability. However, since the 1980s, several studies have shown that climate variability and agricultural changes may already have locally eroded crop genetic diversity. We studied pearl millet diversity in Senegal through a comparison of pearl millet landraces collected 40 years apart. We found that more than 20% of villages visited in 1976 had stopped growing pearl millet. Despite this, its overall genetic diversity has been maintained but differentiation between early- and late-flowering accessions has been reduced. We also found stronger crop-to-wild gene flow than wild-to-crop gene flow and that wild-to-crop gene flow was weaker in 2016 than in 1976. In conclusion, our results highlight genetic homogenization in Senegal. This homogenization within cultivated pearl millet and between wild and cultivated forms is a key factor in genetic erosion and it is often overlooked. Improved assessment and conservation strategies are needed to promote and conserve both wild and cultivated pearl millet diversity.